The Yin and Yang dualistic features of autophagy in thermal burn wound healing. (13th September 2022) - Ripszky Totan, Alexandra; Greabu, Maria; Stanescu-Spinu, Iulia-Ioana; Imre, Marina; Spinu, Tudor-Claudiu; Miricescu, Daniela; Ilinca, Radu; Coculescu, Elena Claudia; Badoiu, Silviu Constantin; Coculescu, Bogdan-Ioan; Albu, Crenguta
Burn healing should be regarded as a dynamic process consisting of two main, interrelated phases: (a) the inflammatory phase when neutrophils and monocytes infiltrate the injury site, through localized vasodilation and fluid extravasation, and (b) the proliferative-remodeling phase, which represents a key event in wound healing. In the skin, both canonical autophagy (induced by starvation, oxidative stress, and environmental aggressions) and non-canonical or selective autophagy have evolved to play a discrete, but, essential, "housekeeping" role, for homeostasis, immune tolerance, and survival. Experimental data supporting the pro-survival roles of autophagy, highlighting its Yang, luminous and positive feature of this complex but insufficient explored molecular pathway, have been reported. Autophagic cell death describes an "excessive" degradation of important cellular components that are necessary for normal cell function. This deadly molecular mechanism brings to light the darker, concealed, Yin feature of autophagy. Autophagy seems to perform dual, conflicting roles in the angiogenesis context, revealing once again, its Yin–Yang features. Autophagy with its Yin–Yang features remains the shadow player, able to decide quietly whether the cell survives or dies.